Креативність, мотивація особистості й взаємозв’язок між ними у графічних дизайнерів та маркетологів - Гімаєва, Ю. А. (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2016)
The article contains the research of factors of graphic designers’ and marketing specialists’ creative activity. The features of nonverbal and verbal creativity, motivation of  success achievement and failures avoidance, personality motivational prole and interconnections between them are studied.